Design a supply chain model for Baghdad Soft Drinks Company - Fadel, Suheir Saad; Mohammed, Mohammed Jasim (Journal of Economics and Administrative Sciences, 2021)
In this paper, a mathematical model was built for the supply chain to reduce production, inventory, and transportation in Baghdad Company for Soft Drink. The linear programming method was used to solve this mathematical model. We reduced the cost of production by reduced the daily work hours, the company do not need the overtime hours to work at the same levels of production, and the costs of storage in the company’s warehouses and agents’ stores have been reduced by making use of the stock correctly, which guarantees reducing costs and preserving products from damage. The units transferred from the company were equal to the units demanded by the agents. The company’s mathematical model also achieved profits by (84,663,769) by reducing the total costs to (825,843,231), while the total cost in the company was (910,507,000)